Pengaruh Penggunaan Google Classroom Terhadap Self-Directed Learning (SDL) Siswa Dalam Pembelajaran Bahasa Inggris - Rizal Akib; Kris Uluelang (Qalam : Jurnal Ilmu Kependidikan, 2019)
This study aims to examine the use of Google Classroom to enhance students’ Self-Directed Learning (SDL) in English Learning. By using quasi experimental study, 50 students were pre-tested before given an English learning supported by the use of Google Classroom during a semester. Following the treatment, the students then post-tested using PRO-SDLS instrument in order to find out whether there was statistically differences between result of pre-test and post-test. The result shows that, there was statistically significant differences in the students’ SDL between the pre-test and the post-test. Therefore, it can be concluded that using Google Classroom can helped students to develop their SDL skill in English Learning.